Emergence of Dengue Virus Infection in Nepal - Gupta, Birendra Prasad; Manandhar, K. D.; Malla, R.; Tamarakar, C.; Mishra, S. K.; Rauniyar, R. (International Journal of Applied Sciences and Biotechnology, 2013)
This article reviews Dengue, a common viral disease in humans and is an emerging public health problem in Tarai Region of Nepal. The most affected are among the poorest populations living in remote, rural areas and urban slums who have even no access for medical treatment, acquired by bite of infected mosquito. Aedes Aegypti infected with dengue virus is the major source of infections for humans and cannot be transmitted from person-to-person because human are the dead end host. DENV-1 was first isolated by Ren Kimura and Susumu Hotta in Japan in 1943. An epidemic of DF involving at least 200,000 cases had occurred between 1942 and 1944 during World War II in Japanese port cities such as Nagasaki, Kobe, and Osaka. First case of dengue was reported in 2004 in Nepal. The seroprevalence study were done in different part of Nepal by IgM antibody capture ELISA and positive rate was highest (50.0%) in Biratnagar, and lowest (19.6%) in Chitwan male to female ratio was 2:1. IgM-positive rate was 29.0% at ages 21-30, 25.4% at ages 11-20 and 23.6% at ages 0-10, but 10.9% at ages 31-40, and ages over 40. There was not significant association between occupation of the patients and positive rate among farmer, labour, service, business and student. The epidemiological studies of Dengue virus infection and the knowledge of the pattern of the disease outbreak can guide therapy and effective preventive measures against this disease. DOI: http://dx.doi.org/10.3126/ijasbt.v1i3.8384 Int J Appl Sci Biotechnol, Vol. 1(3) 2013 : 79-84